Turkish Validation and Reliability of the EORTC QLQ-CR29 Quality of Life Scale for Colorectal Cancer - Akduran, Funda; Durna, Zehra (Turkish Journal of Gastroenterology, 2021)
Background: This study aims to test the validity and reliability of the Turkish version of the European Organization for Research and Treatment of Cancer, Quality of Life Questionnaire-Colorectal Cancer Scale, and to evaluate the relationship between the factors affecting the quality of life in patients with colorectal cancer (CRC). Methods: 117 patients diagnosed with CRC and treated at the Training and Research Hospital were included. A Personal Information Form, questionnaires on the Quality of Life in Cancer Patients, Quality of Life in Patients with CRC, and the Adaptation Scale for Individuals with Ostomy were used. Results: The validity and reliability of the KKHYK scale were found significant (P < .05). From the demographic data of the patients, the differences between 3 sub-dimensions, grouping according to gender, and 2 sub-dimensions were statistically significant. In the characteristics related to the disease, the differences between the groups were significant; for one for the diagnosis time of the disease, 2 dimensions in the adaptation parameter (P < .05). Conclusion: The Turkish version of the scale is a measurement tool with validity and reliability indicators to measure the quality of life of patients with CRC. It was concluded that patients did not have sufficient knowledge about their disease, and that this increased the burden of nursing care.